Modular modeling method and power supply capability evaluation for integrated hydrogen production stations of DC systems - Qi Wu; Qiang Yao; Li Ding; Wei Pei; Wei Deng (Energy Reports, 2022)
Low-voltage DC distribution system has many advantages, such as facilitating the access of DC loads and distributed energies and improving the network’s stability. It has become a new idea for integrated hydrogen production stations. Power supply capacity and small-signal stability are important indexes to evaluate a low-voltage DC integrated system. Based on the master–slave control mode, this paper selects the typical star structure as the research object, constructs the system transfer function through the scalable modular modeling method, and further evaluates the impact of the high-order DC hydrogen production station integrated system on the hydrogen production capacity under the changes of the line length and master station position. The results show that the hydrogen production capacity of the system decreases gradually with the main station moving from side to inside. Finally, a practical example is analyzed by MATLAB/Simulink simulation to verify the accuracy of the theory. This study can provide an effective theoretical method for the structure optimization and integrated parameter design of low-voltage DC system.